Effects of pressure and substrate temperature on the growth of Al-doped ZnO films by pulsed laser deposition - Kek, Reeson; Tan, Kwan Chu; Nee, Chen Hon; Yap, Seong Ling; Koh, Song Foo; Arof, Abdul Kariem; Tou, Teck Yong; Yap, Seong Shan (IOP Publishing, 2020)
Al-doped ZnO (AZO) thin films were deposited on p-Si (100) by pulsed laser deposition from a composite ceramic target (ZnO:Al2O3) by using 355 nm laser at different O2 background pressure and substrate temperature. Upon ablation at laser fluence of 2 Jcm-2, plasma plume consists of Zn neutrals and ions, Al neutrals and O neutral are formed. As the O2 background pressure increases from 3 Pa to 26 Pa, the energy of the plasma species are moderated. The results show that the ions density and velocity reduced significantly above 13 Pa. The velocity of the ions reduced from 14 kms-1 to 11 kms-1 at 13 Pa, while the ions energy reduced from 63 eV to 42 eV respectively. Below 13 Pa, crystalline and homogeneous AZO nanostructured films were formed. Above 13 Pa, the process results in low crystallinity films with higher porosity. The resistivity of the films also increases from 0.1 ohmcm to 24 ohmcm as the pressure increased. At fixed O2 background pressure of 3 Pa, the adatom mobility of atoms on the substrates is altered by substrate heating. The resistivity of the films decreased to 10-3 ohmcm when the substrates are heated to 100 °C-300 °C during deposition. The films with highest carrier density of 1020 cm-3 and carrier mobility of 13 cmV-1 s-1 are achieved at 200 °C. © 2020 The Author(s). Published by IOP Publishing Ltd.